2020
DOI: 10.1186/s12891-020-03572-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of foehn winds on the incidence of severe injuries in southern Bavaria – an analysis of the TraumaRegister DGU®

Abstract: Background: Foehn describes a wind which occurs in areas with close proximity to mountains. The presence of foehn wind is associated with worsening health conditions. This study analyzes the correlation between a foehn typical circulation and the incidence for suffering a severe trauma. Methods: This is a retrospective, multicentre observational register study. The years from 2013 to 2016 were analyzed for the presence of foehn winds. A logistic regression analysis with the number of daily admitted trauma pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Foehn wind is a well-known phenomenon in the Swiss Alpine region, generating a warm, dry, and often severe wind on the leeward downwind side of the mountain, descending from the crest into the valley, and reaching hurricane force wind speeds of 117 km/h (maximum exceeding 200 km/h) [ 24 ]. This meteorological phenomenon can be found all over the world in high mountain regions, such as ‘Halny’ in Poland or ‘Chinook’ in North America [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foehn wind is a well-known phenomenon in the Swiss Alpine region, generating a warm, dry, and often severe wind on the leeward downwind side of the mountain, descending from the crest into the valley, and reaching hurricane force wind speeds of 117 km/h (maximum exceeding 200 km/h) [ 24 ]. This meteorological phenomenon can be found all over the world in high mountain regions, such as ‘Halny’ in Poland or ‘Chinook’ in North America [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although research remains scarce, foehn wind has been associated with a large variety of worsening health conditions, frequently labeled as ‘foehn illness’ [ 25 , 26 ]. These symptoms include migraine and headaches, joint pain, wound pain, sleep disorders, fatigue, concentration problems, anxiety, nausea, paresthesia, an increase in aggressiveness, agitation, depressive states, and suicide attempts [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms include migraine and headaches, joint pain, wound pain, sleep disorders, fatigue, concentration problems, anxiety, nausea, paresthesia, an increase in aggressiveness, agitation, depressive states, and suicide attempts [27][28][29][30][31][32][33][34]. Recently, Greve, et al [25] detected an increase in trauma-related hospital admissions on days with foehn. Some studies have found no effects on health conditions [29,35,36] or even relief of neuropathic pain during Chinook winds [37].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to consider seasonal variations to understand the impact of weather conditions for health services [ 23 ]. In addition to temperature, other meteorological parameters for predicting morbidity and mortality are solar radiation, humidity, wind speed, precipitation, and foehn [ 4 , 6 , 8 , 24 , 25 ]. Following extreme weather events, there is an increased demand for emergency services and an increased mortality risk [ 2 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature extremes induced higher mortality rates among the elderly [ 50 ] and higher cardiovascular mortality [ 51 ]. Also, ambulance activity in Munich was affected by temperature, humidity, sunshine, and precipitation [ 4 ], and severe trauma by foehn winds [ 25 ]. However, the influence of weather conditions on traffic accidents has not yet been studied at all.…”
Section: Introductionmentioning
confidence: 99%